CRITICAL THINKING AND MEANINGFUL LEARNINGS IN ONLINE LEARNING: DO BOTH MAKE INCREASES? - Hasmiah Herawati (Jurnal Pendidikan Ilmu Sosial, 2022)
Crosspuzzle learning is necessary for encouraging students more critical and quickly to understand the material. This study aims to analyze the use of crossword puzzles in the inquiry model by determining the difference between the application of critical thinking and meaningful learning in online learning at SMPN 1 Parepare using crossword puzzle. The research approach was carried out with a sequential explanatory design. This research in the first stage uses quantitative methods, followed by qualitative methods in the second stage. The quantitative method used quasi-experimental data analysis techniques with independent sample-t test on 64 respondents in the control and experimental classes, while the qualitative method was used to extract information using an open questionnaire after the post-test results were got. The results showed that there was a significant difference in the ability of critical thinking and meaningful learning to use the inquiry model (crossword puzzle) got from the t-test results which showed the value of sig.2-tailed 0.000.05 and tcount 4.688 ttable 1.999. This difference is also supported by descriptive data as an average post-test score of 93.28 for the experimental class which comprises 93.75% of respondents in the very good category and 6.25% in the good value category, higher than the average score for the control class of 85.19.